Penerapan Metode Metode MOOSRA dan ROC dalam Rekomendasi Penentuan Handphone Terbaik untuk Pembuatan Konten Youtube - Mesran; Agung Triayudi; Dian Yunita Sihombing; Rosaima Situmorang (STMIK Budi Darma, 2023)
Every day technological advances are increasing and developing, one of which is cellphones. Mobile phones are a technology that users can use to create YouTube content. The increasing development of the technological era from year to year has led to the emergence of cellphone brands with different specifications, making YouTube content users confused in determining the best cellphone. Based on this, the author conducted research to determine the best cellphone for creating YouTube content using the Moosra and Roc methods. We can use the Moosra and Roc method to determine the best cellphone for creating YouTube content, including choosing the brand and specifications of the cellphone. The results achieved in determining the type of cellphone brand and the best quality for creating YouTube content using the MOOSRA and ROC methods. And the final result of this decision support system (DSS) is determining the best brand and quality of cellphone for creating YouTube content. Rank Order Centroid (ROC) Method ROC is a method used to find the weight for each criterion according to its level and the Multi-Object Optimization Method On the basis of Simple Ration Analysis (MOOSRA) is a method that can be used to solve semi-structured and multidisciplinary problems attribute. The research results showed that Alternative A8 (Samsung) was chosen as the best alternative in determining the best cellphone for creating YouTube content with a preference value of 45.5 using the MOOSRA and ROC methods.